Workers education: Conceptual and practical opportunities for adult educators - Tom Nesbit (Adult Education Research Conference, 1993)
This paper describes two research studies that show how adult educators can develop links with, and support workers' educational initiatives, and in so doing, explain the knowledge base of the adult education field. There have been calls at recent North American adult education gatherings for a strengthening of the links between educational researchers and worker activists, and the reintroduction of workers' education to North American adult education discourse. Unlike British and other European adult education movements, modern adult education in the United States and (to a lesser extent) Canada has largely ignored and been separate from workers' education. The published literature has focused on the historical development of both adult and workers' educational institutions and their movement away from social transformation toward more functionalist and technocratic purposes. However, more recently, adult educators have begun to identify the potential of the workplace as a site of educational as well as economic struggle (Candy and Crebert, 1991: Hart, 1992: Simon et al, 1990) and to recognize the benefits in closer cooperation with worker educators (Kumar, 1990; Mantsios, 1990). This paper describes two research studies that challenge commonly held assumptions about workplace education, the production of knowledge, and the relationships between work, learning and experience – all crucial issues for adult educators. Most importantly, they force adult educators to face the question "Education for whom and to what end?" By taking the opportunities that workers' education presents, adult educators can develop their understanding of workers' educational issues and extend and deepen the relationships between the two fields.